Asarone and Metformin Modulates the Oxidant- Antioxidant Imbalance on Experimentally Induced Hepatocellular Carcinoma during Diabetic Condition - Das, Bhrigu Kumar; Gadad, Pramod Channabasappa (Indian Journal of Pharmaceutical Education and Research, 2020)
Aim: The aim of the present study was planned to investigate the efficacy of asarone and metformin HCl as an antioxidant on experimentally induced diabetic-hepatocellular carcinoma (HCC) condition in male Wistar rats. Methods: Diabetes was induced in experimental rats by single intraperitoneal injection of streptozotocin (STZ; 55 mg/kg b.w.). Following two weeks of STZ injection, the diabetic-HCC condition was simulated in the rats with a single intraperitoneal dose of diethylnitrosamine (DEN; 200 mg/ kg b.w.). The α-and β-asarone combination in the ratio of 1:1 (50 μg/kg b.w.) and metformin HCl (250 mg/kg b.w.) treatment were orally given to the diabetic-HCC rats up to 18-weeks. At the end of the experimental period, rats were sacrificed after the withdrawal of blood for biochemical and liver samples were isolated for the antioxidant and histopathological analysis. Results: The elevated levels of liver function test such as alkaline phosphatase, bilirubin and decreased levels of total protein, albumin and globulin indicated the hepatic damage in the diabetic-HCC rats. Further, the STZ+DEN-induced oxidative stress was confirmed by the elevated levels of lipid peroxidation (LPO) and decreased levels of superoxide dismutase (SOD), catalase (CAT), glutathione peroxidase (GPx), reduced glutathione (GSH) and Vitamin-C. Treatment with asarone and metformin significantly ameliorated the STZ+DEN-induced hepatic damage and oxidative stress. Histopathological evidence also showed recovery of the hepatic architecture in diabetic- HCC rats treated with asarone and metformin. Conclusion: Asarone and metformin exhibit good hepatoprotective and antioxidant potential against STZ+DEN-induced HCC in rats.
Keywords: Asarone; Diethylnitrosamine; Metformin; Oxidative stress; Streptozotocin